Engineering a unique Multi-tasking polymer that specifically prevents rhodamine B and fluoride ion toxicity with Anti-bacterial responses against MRSA. (5th August 2022) - Kumar, Rajan; Dey, Rajib; Kalita, Tanmoy; Pariyal, Sanjib; Sankar Goswami, Bijoy; Haldar, Jayanta; Shunmugam, Raja
Graphical abstract: The ionic cross-linked polymer represent a model where it can be implemented for three different and distinct water filteration function to adsorbtion of dye, fluoride removal via ion exchange process and water disinfection. Abstract: There is always a necessity for the invention of materials that can show improved efficiency to adsorption of organic dye and pigments and fluoride removal incubating the additional properties like antimicrobial responses when the finding is related to water remediation. We elaborated cross-linked ionic models where the crosslinker was tuned from 1, 3-dibromopropane to 1, 9-dibromononane, to invent multifunctional metal-free, water-immiscible, and easy-to-handle material. The synthesized cross-linked and ionic polymeric materials were well characterized using the standard spectroscopic and analytical techniques - NMR, ATR-FTIR, APC, and FE-SEM. The cross-linked polymers invoked for water remediation showed good potency in removing water-miscible wastes like rhodamine B (RhB) and fluoride. The analysis revealed 50 mg PVPC3 with 1, 3-dibromopropane as crosslinker when treated with 10 ppm per 50 mL fluoride solution showed effective removal of 9.6 ppm fluoride, and 60 mg PVPC9 with 1, 9-dibromononane as crosslinker removed around 78% RhB. Therefore with backbone PVP constant, the efficiency in removing different classes of waste can be tuned accordingly. Moreover, the ionic cross-linked polymers showed good responses against Methicillin-resistant Staphylococcus aureus (MRSA).